Adjuvant Therapy Reduces Fat Mass Loss during Exercise Prescription in Breast Cancer Survivors - Gabriele Mascherini; Benedetta Tosi; Chiara Giannelli; Elena Ermini; Leonardo Osti; Giorgio Galanti (Journal of Functional Morphology and Kinesiology, 2020)
Improvements in cancer care over the years have increased the numbers of cancer survivors. Therefore, quality of life, fat mass management and physical activity are growing areas of interest in these people. After the surgical removal of a breast cancer, adjuvant therapy remains anyway a common strategy. The aim of this study was to assess how adjuvant therapy can affect the effectiveness of an unsupervised exercise program. Forty-two women were enrolled (52.0 ± 10.1 years). Assessments performed at baseline and after six months of exercise prescription were body composition, health-related quality of life, aerobic capacity by Six-Minute Walk Test, limbs strength by hand grip and chair test and flexibility by sit and reach. Statistical analyses were conducted by ANOVA tests and multiple regression. Improvements in body composition, physical fitness and quality of life (physical functioning, general health, social functioning and mental health items) were found. The percentage change in fat mass has been associated with adjuvant cancer therapy (intercept = −0.016; b = 8.629; p < 0.05). An unsupervised exercise prescription program improves body composition, physical fitness and health-related quality of life in breast cancer survivors. Adjuvant therapy in cancer slows down the effectiveness of an exercise program in the loss of fat mass.